Experimental economics: Methods, problems and promise - Davis, Douglas D.; Holt, Charles A. (Estudios Económicos de El Colegio de México, 1993)
The purpose of this paper is to discuss the growing importance of experimentation in economic analysis. We present a variety of economic issues that have been explored with laboratory techniques. We also address some common objections to experimentation, as well as some of the principal lessons that have been learned.